Outcome after cardiopulmonary resuscitation in patients with congenital heart disease. Issue 5 (August 2018) - Van Puyvelde, Tim; Ameloot, Koen; Roggen, Mieke; Troost, Els; Gewillig, Marc; Budts, Werner; Van De Bruaene, Alexander
Background: Outcome after cardiopulmonary resuscitation (CPR) in patients with underlying congenital heart disease is uncertain. This study aimed at evaluating outcome after CPR in patients with underlying congenital heart disease, factors related to worse outcome after CPR and whether survivors of sudden cardiac death (SCD) have a worse outcome when compared to an age, gender and disease-matched control population. Methods: Between 1984 and 2015, all patients with congenital heart disease who received in or out-of-hospital CPR were identified from the database of congenital heart disease from the University Hospitals Leuven. Postoperative and neonatal (<6 months of age) CPR was excluded. For each survivor of SCD, two control patients matched for gender, age and underlying heart defect were included in the study. Results: Thirty-eight patients (66% men; median age 25 years (interquartile range 9–40); 68% out-of-hospital) were identified, of which 27 (66%) survived the event. The main cause of SCD was ventricular tachycardia or fibrillation ( n =21). Heart defect complexity (odds ratio (OR) 5.1; 95% confidence interval (CI) 1.2–21.9; P =0.027), pulmonary hypertension (OR 13.8; 95% CI 2.1–89.5; P =0.006) and time to return of spontaneous circulation (OR 1.1; 95% CI 1.0–1.1; P =0.046) were related to worse outcome. Survivors of SCD had a worse prognosis when compared to an age, gender and disease-matched control group (5-year survival 76% vs. 98%; P =0.002). Conclusions: The complexity of underlying heart defect, pulmonary hypertension and time to return of spontaneous circulation are related to worse outcome in the case of CPR. Survivors of SCD have a worse outcome when compared to matched controls, indicating the need for adequate implantable cardioverter defibrillator indication assessment and for stringent follow-up of patients with worsening haemodynamics.